Pengaruh Kepuasan Pelanggan, Social Media Marketing dan Word of Mouth Terhadap Keputusan Pembelian - Marisa Adellia Lubis; Tika Nirmala Sari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the influence of customer satisfaction, social media marketing, and word of mouth both partially and simultaneously on purchasing decisions at PT Mitra Jaya Perabot. The study uses a quantitative approach with an associative method. The study population is consumers of PT Mitra Jaya Perabot who have made purchases with a sample of 120 respondents using the Lemeshow formula and purposive sampling technique. The results of the study indicate that partially the Customer Satisfaction variable does not affect purchasing decisions where (t count < t table) is 969 < 1.980 and Social Media Marketing also does not affect purchasing decisions where (t count < t table) is 1.429 < 1.980. On the other hand, Word of Mouth has a positive and significant effect on purchasing decisions with a value (t count> t table) of 6.178> 1.980. Simultaneously, these three variables have a positive and significant effect on purchasing decisions of consumers of PT Mitra Jaya Perabot. These results indicate that Word of Mouth is the most dominant factor in influencing purchasing decisions, so companies are advised to strengthen communication strategies and relationships with customers through recommendation-based promotions.